Metagenome-Sourced Microbial Chitinases as Potential Insecticide Proteins - Berini, Francesca; Casartelli, Morena; Montali, Aurora; Reguzzoni, Marcella; Tettamanti, Gianluca; Marinelli, Flavia (Frontiers in Microbiology, 2019)
Microbial chitinases are gaining interest as promising candidates for controlling plant pests. These enzymes can be used directly as biocontrol agents as well as in combination with chemical pesticides or other biopesticides, reducing their environmental impact and/or enhancing their efficacy. Chitinolytic enzymes can target two different structures in insects: the cuticle and the peritrophic matrix (PM). PM, formed by chitin fibrils connected to glycoproteins and proteoglycans, represents a physical barrier that plays an essential role in midgut physiology and insect digestion, and protects the absorptive midgut epithelium from food abrasion or pathogen infections. In this paper, we investigate how two recently discovered metagenome-sourced chitinases (Chi18H8 and 53D1) affect, in vitro and in vivo, the PM integrity of Bombyx mori, a model system among Lepidoptera. The two chitinases were produced in Escherichia coli or, alternatively, in the unconventional -but more environmentally acceptable- Streptomyces coelicolor. Although both the proteins dramatically altered the structure of B. mori PM in vitro, when administered orally only 53D1 caused adverse and marked effects on larval growth and development, inducing mortality and reducing pupal weight. These in vivo results demonstrate that 53D1 is a promising candidate as insecticide protein.